Amino acid substitutions in the coat protein result in loss of insect transmissibility of a plant virus. - Atreya, P L (1991)
Amino acids near the N terminus of the coat protein of tobacco vein mottling virus were deleted or altered by site-directed mutagenesis to determine the effect on aphid transmissibility of the virus. Deletion of a three amino acid sequence Asp-Ala-Gly, which is conserved in aphid-transmissible potyvirus isolates, abolished transmission. The mutation Ala----Thr in this triplet drastically reduced transmission, whereas the mutation Asp----Asn had no effect, and the mutation Asp----Lys consistently reverted to the wild-type residue. The mutation Lys----Glu, in the residue adjacent to the glycine of the triplet, drastically reduced transmission, whereas the mutation Gln----Pro, seven residues downstream from the glycine had no effect. Comparison of the sequences of other potyviruses suggests that the presence of a glycine residue at the third position of the Asp-Ala-Gly triplet is critical for aphid transmissibility and that certain changes in the residues adjacent to this position abolish or greatly reduce aphid transmissibility.